Analisis rencana strategi BMT mu’awanah dan BMT mandiri - Putra, Muhammad Arvian Rivanda (Maliki Interdisciplinary Journal, 2023)
Sharia financial institutions are financial institutions that operate based on Islamic economic principles. One Sharia financial institution currently developing quite significantly is Baitul Maal wat Tamwil (BMT). However, behind the significant development of BMT, there is a strategic plan being implemented by each BMT. This research aims to analyze the strategic plans implemented by BMT Mandiri and BMT Mu’awanah. The research results show that the strategic plans of BMT Mandiri and BMT Mu’awanah show that both have a strong commitment to Sharia principles in their economic activities, focus on empowering small and medium entrepreneurs, and implement a meaningful social approach in helping those who are less fortunate/lucky (dhuafa). Through this emphasis, both BMTs have a great opportunity to improve the quality of membership, attract individuals and businesses who wish to transact according to sharia principles and sustainably contribute to social and broader community welfare.